Autologous Fat Transfer Art, Science, and Clinical Practice - Shiffman, Melvin A.; Shiffman, Melvin A. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
The book covers all aspects of autologous fat transfer including the history of fat transfer, the history of autologous fat survival, a variety of aesthetic and plastic procedures of the face and body, noncosmetic applications of fat transfer, preoperative care, complications, and medical-legal aspects. The contributors are international experts in the field of autologous fat transfer. The Table of Contents shows the variety of subjects. The book is intended for residents and fellows, practicing and highly experienced cosmetic surgeons, and surgeons in the fields of plastic surgery, general surgery, otolaryngology, ophthalmology, oral-maxillofacial surgery, neurosurgery, orthopedic surgery, and other surgical subspecialties.